2012
DOI: 10.1242/jeb.076356
|View full text |Cite
|
Sign up to set email alerts
|

Cellular damage as induced by high temperature is dependent on rate of temperature change – investigating consequences of ramping rates on molecular and organismal phenotypes in Drosophila melanogaster Meigen 1830

Abstract: SUMMARYEcological relevance and repeatability of results obtained in different laboratories are key issues when assessing thermal tolerance of ectotherms. Traditionally, assays have used acute exposures to extreme temperatures. The outcomes of ecologically more relevant ramping experiments, however, are dependent on the rate of temperature change leading to uncertainty of the causal factor for loss of function. Here, we test the physiological consequences of exposing female Drosophila melanogaster to gradually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 33 publications
2
45
0
3
Order By: Relevance
“…That is, the duration of exposure at higher temperatures had a highly significant impact (P>0.0001) on survival, but only marginally significant (P = 0.0423) at lower temperatures. We speculate that at higher temperatures the severity of tissue injury which could not be repaired was probably higher [5], and cell damage would occur [67]. In contrast, Chapman [53] found that the duration of exposure affected insect survival at low temperatures.…”
Section: Discussionmentioning
confidence: 88%
“…That is, the duration of exposure at higher temperatures had a highly significant impact (P>0.0001) on survival, but only marginally significant (P = 0.0423) at lower temperatures. We speculate that at higher temperatures the severity of tissue injury which could not be repaired was probably higher [5], and cell damage would occur [67]. In contrast, Chapman [53] found that the duration of exposure affected insect survival at low temperatures.…”
Section: Discussionmentioning
confidence: 88%
“…The rate of heating has been suggested to influence heat tolerance (Terblanche et al ., ), with slower temperature rate better at improving heat tolerance than fast rates. Slower ramping rates likely give ample time for insects to physiologically adjust (Sørensen et al ., ), for example through expression of Hsps. Therefore, during HKDT experiments, the sudden heat shock may have constrained the insects to mount compensatory adjustments physiologically (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We are concerned that studies used to infer the thermal limits of different aquatic insects often focus on short-term acute thermal challenges (critical temperature or CT max type experiments) or thermal ramping rates (see Sorensen et al, 2013) that are not typically experienced by organisms in nature. Despite excellent work showing the importance of temporal aspects of thermal change and exposure durations (Angilletta, 2009;Schulte et al, 2011;Dillon and Frazier, 2013), short-term thermal challenges remain the most common experimental approach used to study thermal physiology.…”
Section: Introductionmentioning
confidence: 99%